PENGATURAN SANKSI PIDANA TERHADAP PERPAJAKAN BERDASARKAN UNDANG UNDANG PERPAJAKAN: Denny Setiawan - admin, admin (Reformasi Hukum, 2018)
Taxes are the dues levied by the state either by the central government and local government based on laws and regulations for the management of tax collection implies the transfer of funds from the private sector to the state sector and intended for purposes of general government financing in order to carry out functions of government. The problem in this writing is why criminal sanctions are needed in the field of taxation, with the aim of writing to study tax criminal sanctions. The research method used this thesis is a normative. Data analysis techniques presented in descriptive form. Research shows that the regulation of criminal sanctions against tax under Act No. 28 of 2007.